Analisis Pengaruh Penggunaan LPG sebagai Bahan Bakar Alternatif terhadap Performansi dan Efisiensi Mesin Bensin - Irvan Hendrawan Surya Dinata; Jufrizal Jufrizal; Darianto Darianto; Tino Hermanto; Bobby Umroh; Nurdiana Nurdiana (CV. IRA PUBLISHING, 2025)
This study investigates the effect of using Liquefied Petroleum Gas (LPG) as an alternative fuel to Pertalite on the performance, energy efficiency, and operating cost of a 6.5 HP gasoline engine-driven water pump. Experiments were conducted at three engine operating conditions: minimum, average, and maximum engine speeds. The evaluated parameters included engine speed, water discharge, hydraulic power, shaft power, brake specific fuel consumption (BSFC), thermal efficiency, overall system efficiency, and fuel operating costs. The results indicate that the pump's hydraulic performance, as measured by water discharge and hydraulic power, is not significantly affected by the type of fuel used. However, engines that use Pertalite tend to have slightly better thermal and system efficiencies than LPG engines. From an economic perspective, LPG offers a substantial advantage, with lower operating and energy costs per unit of power. Therefore, despite Pertalite's slightly superior technical efficiency, LPG is a more economical alternative fuel for long-duration water pump applications.